Molecular tools for probing the microbiome. (October 2022) - Torres, Marcelo Der Torossian; de la Fuente-Nunez, Cesar
Abstract: The microbiome plays essential roles in health and disease. Our understanding of the imbalances that can arise in the microbiome and their consequences is held back by a lack of technologies that selectively knock out members of these microbial communities. Antibiotics and fecal transplants, the existing methods for manipulating the microbiota of the gastrointestinal tract, are not sufficiently pinpointed to reveal how particular microbial genes, strains, or species affect human health. A toolset for the precise manipulation of the microbiome could significantly advance disease diagnosis and treatment. Here, we provide an overview of current and future strategies for the development of molecular tools that can be used to probe the microbiome without producing off-target effects. Highlights: Molecular tools need to be developed to enable precise microbiome engineering. Computational-experimental frameworks have been used for the discovery of molecular tools for engineering microbiomes. CRISPR, bacteriophages, and small molecules represent promising current technologies for reprogramming microbiomes.